Cleft palate repair and variations - Karoon Agrawal (Indian Journal of Plastic Surgery, 2009)
Cleft palate affects almost every function of the face except vision. Today a child born with cleft palate with or without cleft lip should not be considered as unfortunate, because surgical repair of cleft palate has reached a highly satisfactory level. However for an average cleft surgeon palatoplasty remains an enigma. The surgery differs from centre to centre and surgeon to surgeon. However there is general agreement that palatoplasty (soft palate at least) should be performed between 6-12 months of age. Basically there are three groups of palatoplasty techniques. One is for hard palate repair, second for soft palate repair and the third based on the surgical schedule. Hard palate repair techniques are Veau-Wardill-Kilner V-Y, von Langenbeck, two-flap, Aleveolar extension palatoplasty, vomer flap, raw area free palatoplasty etc. The soft palate techniques are intravelar veloplasty, double opposing Z-plasty, radical muscle dissection, primary pharyngeal flap etc. And the protocol based techniques are Schweckendiek's, Malek's, whole in one, modified schedule with palatoplasty before lip repair etc. One should also know the effect of each technique on maxillofacial growth and speech. The ideal technique of palatoplasty is the one which gives perfect speech without affecting the maxillofacial growth and hearing. The techniques are still evolving because we are yet to design an ideal one. It is always good to know all the techniques and variations so that one can choose whichever gives the best result in one's hands. A large number of techniques are available in literature, and also every surgeon incorporates his own modification to make it a variation. However there are some basic techniques, which are described in details which are used in various centres. Some of the important variations are also described.